Can compact rail transit corridors transform the automobile city? Planning for more sustainable travel in Los Angeles - Houston, Douglas; Boarnet, Marlon G; Ferguson, Gavin; Spears, Steven (Urban studies (Edinburgh, Scotland), 2015)
Directing growth towards compact rail corridors has become a key strategy for redirecting autooriented regions towards denser, mixed-use communities that support sustainable travel. Few have examined how travel of near-rail residents varies within corridors or whether corridor land use–travel interactions diverge from regional averages. The Los Angeles region has made substantial investments in transit-oriented development, and our survey analysis indicates that although rail corridor residents drove less and rode public transit more than the county average, households in an older subway corridor with more near-transit development had about 11 fewer daily miles driven and higher transit ridership than households along a newer light rail line, a difference likely associated with development patterns and the composition and preferences of residents. Rail transit corridors are not created equally, and transit providers and community planners should consider the social and development context of corridors in efforts to improve transit access and maximise development.